Rapid determination of Papaver somniferum alkaloids in process streams using monolithic column high-performance liquid chromatography with chemiluminescence detection - Costin, J.; Lewis, Simon; Percell, S.; Waddell, L.; Francis, P.; Barnett, N. (Elsevier, 2007)
We have combined high-performance liquid chromatography (HPLC) separations using a monolithic column with acidic potassium permanganate and tris(2,2'-bipyridyl)ruthenium(II) chemiluminescence detection in a rapid and highly sensitive method to monitor the process of extracting opiate alkaloids from Papaver somniferum. Due to the high flow rates allowed with the monolithic column and the inherent selectivity of the chemiluminescence reactions, the four predominant alkaloids - morphine, codeine, oripavine and thebaine - were determined in less than 2 min. The results obtained with numerous process samples compared favourable with those of the standard HPLC methodology. Limits of detection were 11010 M, 51010 M, 51010M and 1109 M, for morphine, codeine, oripavine and thebaine, respectively.